Foreign Direct Investment, Export and Economic Growth: An Evidence from Nepal - Subedi, Prakash; Kharel, Suman; Poudel, Jiban Mani (Academia Journal of Humanities & Social Sciences, 2024)
The aim of this paper is to analyze and evaluate the present status of foreign direct investment (FDI) in Nepal concentrating economic growth and export boost. Developing nations like Nepal derive significant advantages from foreign investment, fostering economic advancement through the attraction of external capital, entrepreneurial skills, expanding market spaces, and technology transfer. Nepal has witnessed an upsurge in FDI since the 1990s, primarily attributable to the implementation of liberal economic policies by the government. The enactment of the Foreign Investment Technology Transfer Act (FITTA) has further sustained the investment environment in Nepal. This paper analyzes and evaluates the role of FDI in driving Nepal’s economic growth and export activities. Employing correlation analysis and an ordinary linear regression model, the impact of FDI on Gross Domestic Product (GDP) and exports is measured. Given the documented FDI inflows since the 1990s, this research concentrates on the period from 2010/11 to 2022/23 to measure FDI’s impact. The findings of this investigation reveal a positive correlation between FDI, GDP and the country’s export growth.